Dança e música : por uma educação humanizadora em prática musical coletiva - Sanchez, Melina Fernandes (2009)
This Master s Dissertation introduces a dialogue between music and dance languages in a collective music practice context, more specifically in a community orchestra. With this purpose, the researcher, dancer and dance educator shares her own experiences in the field of Music Education and discusses the interaction developed with some members of the Experimental Orchestra of the Federal University of São Carlos (São Paulo state). The aim of this research is to discuss how experiences and reflections of dance activities can contribute for self perception, perception of the other and perception of music practice in order to benefit humanizing Education. The research includes eight movement themes related to the Choreological study proposed by Preston-Dunlop. They are: Body - whole and parts; Space kinesphere; Space octahedron; Space Shape; Space Projection; Dynamics Time; Dynamics Weight; and Relationships. The interaction meetings included experiences and reflections of dance activities. The methodological approach for the interaction was the context-based Art in Education/ Dance which articulates authors as Paulo Freire and Rudolf Laban main references in this research as well as Fiori, Gainza, Kater, Koellreutter and Marques. Results discuss the speeches from conversation circles proposed at the end of each interaction meeting. Presented in a discursive way, results include the researchereducator s reflections articulated with theoretical references, and point out the contributions of this process for self perception, perception of the other and perception of music collective practice.